2022
DOI: 10.1523/jneurosci.1468-21.2022
|View full text |Cite|
|
Sign up to set email alerts
|

Improved Speech Hearing in Noise with Invasive Electrical Brain Stimulation

Abstract: Speech perception in noise is a challenging everyday task with which many listeners have difficulty. Here, we report a case in which electrical brain stimulation of implanted intracranial electrodes in the left planum temporale (PT) of a neurosurgical patient significantly and reliably improved subjective quality (up to 50%) and objective intelligibility (up to 97%) of speech in noise perception. Stimulation resulted in a selective enhancement of speech sounds compared with the background noises. The receptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 83 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…Invasive recordings in patients with epilepsy have found that larger responses to noisy speech in STC in patients with better task performance ( Nourski et al, 2019 ); that STC restores missing acoustic content from the incoming speech signal ( Leonard et al, 2016 ); and that STC responses to visual speech correspond to its perceptual benefit for noisy auditory speech ( Karas et al, 2019 ). Magnetoencephalographic recordings track the maintenance of online speech representations in STC for the resolution of ambiguous speech tokens ( Gwilliams et al, 2018 ) and electrical stimulation of STC results in improved speech-in-noise perception ( Patel et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Invasive recordings in patients with epilepsy have found that larger responses to noisy speech in STC in patients with better task performance ( Nourski et al, 2019 ); that STC restores missing acoustic content from the incoming speech signal ( Leonard et al, 2016 ); and that STC responses to visual speech correspond to its perceptual benefit for noisy auditory speech ( Karas et al, 2019 ). Magnetoencephalographic recordings track the maintenance of online speech representations in STC for the resolution of ambiguous speech tokens ( Gwilliams et al, 2018 ) and electrical stimulation of STC results in improved speech-in-noise perception ( Patel et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…More invasively, there is great interest in implanted brain-computer interfaces as remedies for communication deficits and to compensate for lost peripheral sensory function ( Beauchamp et al, 2020 ; Moses et al, 2021 ; Vansteensel and Jarosiewicz, 2020 ). Electrical stimulation of intracranial electrodes implanted in superior temporal cortex of a single patient resulted in improved speech-in-noise perception ( Patel et al, 2022 ). A neural prosthetic implanted in superior temporal cortex could help normalize the pattern of activity to make it easier for patients to understand speech.…”
Section: Discussionmentioning
confidence: 99%